TRADISI PECOTAN DALAM PANDANGAN ILMU SOSIOLOGI DI PAITON PROBOLINGGO: Studi kritis sosiologis - Alwi, Bashori (MAQASHID, 2020)
The invite tradition in some areas, including in Karang Anom is very interesting to be discussed, because in addition to the people who organize a walimah event giving invitations, they also include goods in the form of cigarettes / soap in the invitation. This tradition is known as pecotan tradition. It is very interesting to discuss in the repertoire of scholars today. Because pecotan tradition indirectly 'forcing' the recipient to bring a reply in the form of money while attending a walimah event. Sociolgi view it as a social fact that occurs in society especially coral society Karang Anom, pecotan not just ordinary tradition, but it is inheritance of ancestor which is difficult to be abandoned, although impressed for some people, but on the other side there is high social value that is existence of mutual help helping people around the community.